(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
The physical culture of the general education school (UTM), its various activities and the planned implementation of public health work, will create the opportunity to form the physical culture of the students, to live in different age periods of their lives with healthy, disease-free biological aging.